A case report of neonatal alloimmune thrombocytopenic purpura: the importance of correct diagnosis for future pregnancies - Fontão-Wendel, Rita; Wendel, Silvano; Odone, Vicente; Carneiro, Jorge David; Silva, Leandra; Isfer, Eduardo (São Paulo Medical Journal, 2005)
CONTEXT: Neonatal alloimmune thrombocyto- penic purpura (NAITP) is a neonatal disorder characterized by maternal alloimmunization against fetal platelet antigens inherited from the father. Intracranial hemorrhage leading to death or permanent neurological disability may occur in the fetus. CASE REPORT: A healthy 30-year-old woman gave birth to her first baby by cesarean after an uneventful 36-week pregnancy. Ten hours after birth, the infant presented severe petechiae, with platelet count of 8 x 103/µl. The mother’s platelet count was normal (180 x 103/µl). The infant re- ceived intravenous immunoglobulin and was dis- charged 18 days later, with platelet count of 100 x 103/µl. The cause of thrombocytopenia was not elucidated at that time. One year later, the infant died of neuroblastoma. Since the parents wanted another child, they were referred for investigation of this thrombocytopenia. Platelet genotyping and platelet antibody screening were performed, showing total HPA-1 system mismatch between mother (HPA-1b1b) and father (HPA-1a1a), with anti-HPA-1a antibodies in the mother’s serum. We concluded that the first baby was born with NAITP. Thus, in the second pregnancy, the mother was treated with several infusions of intravenous immunoglobulin. Careful ultrasound monitoring was performed, with normal results for mother and fetus throughout the pregnancy. The second baby was born by cesarean at 39 weeks, presenting 92x103 platelets/µl six hours after birth. The baby’s platelets were genotyped as HPA-1a1b and the mother’s serum again showed anti-HPA-1a antibodies. No clinical bleeding was observed. Intravenous immunoglobulin therapy was an effective treatment for preventing NAITP in the second baby.